2017
DOI: 10.1530/eje-17-0404
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-responsive non-coding small RNAs extend the potential of HCG stimulation to act as a bioassay of androgen sufficiency

Abstract: Background: It is unclear whether a short-term change in circulating androgens is associated with changes in the transcriptome of the peripheral blood mononuclear cells (PBMC). Aims and methods:To explore the effect of hCG stimulation on the PBMC transcriptome, 12 boys with a median age (range) of 0.7 years (0.3, 11.2) who received intramuscular hCG 1500u on 3 consecutive days as part of their investigations underwent transcriptomic array analysis on RNA extracted from peripheral blood mononuclear cells before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, there is a need to explore more effective methods of selecting cases that may display androgen insensitivity. Whilst in the past this has involved assessment of AR binding in genital skin fibroblasts [119,120] or measurement of circulating androgen responsive proteins in response to androgen stimulation [121,122], in the future it may be possible to use other methods such as measurement of apolipoprotein D in genital skin fibroblasts [117] or assessment of changes in an androgen responsive transcriptome within circulating polymorphonuclear blood cells [123]. Variants in several other genes, such as INSL3, AMH, AMHR2, MAMLD1, TAC3, WDR11, TACR3, HS6ST1, CHD7, may also contribute to DSD [124].…”
Section: Disorders Of Androgen Actionmentioning
confidence: 99%
“…However, there is a need to explore more effective methods of selecting cases that may display androgen insensitivity. Whilst in the past this has involved assessment of AR binding in genital skin fibroblasts [119,120] or measurement of circulating androgen responsive proteins in response to androgen stimulation [121,122], in the future it may be possible to use other methods such as measurement of apolipoprotein D in genital skin fibroblasts [117] or assessment of changes in an androgen responsive transcriptome within circulating polymorphonuclear blood cells [123]. Variants in several other genes, such as INSL3, AMH, AMHR2, MAMLD1, TAC3, WDR11, TACR3, HS6ST1, CHD7, may also contribute to DSD [124].…”
Section: Disorders Of Androgen Actionmentioning
confidence: 99%
“…An extended investigation where epigenetic regulation of AR was assessed at both transcription and translation levels resulted in molecular diagnosis of AIS type II due to the production of aberrant AR promoter transcripts [Hornig et al, 2018]. In another study, the existence of an androgen-responsive transcriptome was also hypothesised due to the identification of several non-coding RNAs that displayed different expression levels before and after hCG stimulation in boys with a DSD phenotype [Rodie et al, 2017]. Given the capability of WGS to iden-tify CNV, SNVs, and INDELs throughout the genome, it is possible to reach a better understanding of DSD mechanisms although the complexity of variants would render interpretation difficult [Bocher et al, 2020].…”
Section: Diagnostic Technologies In Geneticsmentioning
confidence: 99%
“…In the past, this has involved assessment of AR binding in genital skin fibroblasts [Evans et al, 1984], measurement of circulating androgen responsive proteins in response to androgen stimulation [Sinnecker et al, 1997;Bertelloni et al, 1997], or even clinical assessment of the genitalia in response to androgen stimulation [Stancampiano et al, 2022]. However, it may be possible to use other methods such as measurement of apolipoprotein D in genital skin fibroblasts [Hornig et al, 2016] or an androgen responsive transcriptome within circulating polymorphonuclear blood cells before and after androgen exposure [Rodie et al, 2017]. Although there are differences in the AR residual function among the AIS phenotypes, no difference has been observed in the hormonal levels across AIS phenotypes [Ahmed et al, 1999;Arnhol et al, 2011].…”
Section: Androgen Insensitivitymentioning
confidence: 99%
“…Androgen sensitivity can be also assessed by measuring change in androgen responsive circulating proteins such as SHBG following androgen exposure but this is rarely performed in clinical practice as the response can be very variable. There may be other methods of assessing tissue responsiveness to androgens including the measurement of androgen responsive proteins in genital skin fibroblasts 100 or the assessment of the androgen responsive transcriptome 101 but their clinical utility requires further exploration. AR analysis may reveal a causative gene variant in over 90% of cases with a CAIS phenotype but given that only 20% of cases with a PAIS phenotype have a variant in the coding region of AR , 102 there is a need to improve the diagnosis of this condition especially as it has been reported that the gene variants in AR may exist beyond the coding sequence 100 .…”
Section: Xy Dsd With Normal Testosterone Normal Precursors and Normal Dhtmentioning
confidence: 99%